Influence of certain rhizosphere fungi together with Rhizoctonia solani and Meloidogyne incognita on germination of 'Pusa Ruby' tomato seeds - S.K. SAXENA, REKHA ARY A and (Indian Phytopathology, 2002)
Studies were carried out to determine the effect of Aspergillus flavus, Epicoccum purpurascens [Epicoccum nigrum], Penicillium vermiculatum, Rhizopus nigricans [Rhizopus stolonifer], Rhizoctonia solani and Meloidogyne incognita on the germination ofseeds of tomato cv. Pusa Ruby. Plants were infected with different inoculum levels (1, 2, 3 and 5 g) of the fungi either separately or in combination with R. solani (5 g) and M. incognita (1000 J2). All the fungi adversely affected the seed germinationalmost in all the treatments in the order (least severe first) A. flavus < P. vermiculatum < E. purpurascens < Rhizopus stolonifer. A. flavus, P. vermiculatum and E. purpurascens reduced the effects of both Rhizoctonia solani and M. incognita infection either separately or in combinations. Rhizopus stolonifer adversely affected seed germination in all cases.